Deixis Used in the Writing Text by the Fourth Semester Students of STKIP PGRI Tulungagung - Umdatul Khoirot (STKIP PGRI Tulungagung, 2018)
Deixis is clearly a form of referring that is tied to the speaker´s context which leads us to the concept of deictic centre. The deictic centre can be divided into certain ‘sub-centres’: (1) person deixis; (2) time deixis; (3) place deixis; (4) discourse deixis; and (5) social deixis. This research provides descriptive knowledge of the way in using deixis of fourth semester students of STKIP PGRI Tulungagung.This research is a descriptive qualitative for it describes deixis found on the written texts made by C class of fourth semester in English department both group A and B. Furthermore, this research is called qualitative because this research has soft data, it is in the form of words, and it provides rich description and analysis of the data.Person deixis can be found as: subject, object, possessive adjective, reflexive or emphatic pronoun, name of person, definite and indefinite noun. Furthermore, place deixis in students’ writing can be found only in word where as adverb of place. In addition, time deixis can be seen in the form of adverb of frequency, noun phrase, adjective of time, adverb of time, numeral adjective, and temporal conjunction.